An evaluation of macroinvertebrate-based biomonitoring and ecotoxicological assessments of deteriorating environmental water quality in the Swartkops River, South Africa - Odume, Oghenekaro Nelson (Rhodes University, Faculty of Science, Institute for Water Research, 2014)
Freshwater resources are increasingly subject to pollution because of escalating human population growth, accompanied by urbanisation, industrialisation, and the increased demand for food. Consequently, freshwater quality, and aquatic ecosystem structure and function have been severely impaired. The Swartkops River, which drains an urbanised and industrialised catchment in the Eastern Cape of South Africa, is no exception. An integrated environmental water quality (EWQ) approach is needed to measure the impacts of deteriorating water quality on its aquatic ecosystem structure and function to sustain these vital ecosystem-attributes. In this study, an integrated EWQ approach, which included i) analysis of water physico-chemical variables; ii) macroinvertebrate-based family-level taxonomic- and traits-based community analysis; iii) Chironomidae species-level taxonomic- and traits-based community analysis; iv) Chironomidae deformity-based sub-lethal analysis; and v) experimental investigation of long-term wastewater effluent effects, using model stream ecosystems, were applied to investigate environmental water quality in the Swartkops River. One upstream reference site and three downstream sites in the Swartkops River were monitored over a period of three years (August 2009 "“ September 2012). The family-level taxonomic community responses based on the South African Scoring System version 5 (SASS5) and a newly developed Swartkops multimetric index indicated very poor river health conditions for the three downstream sites, compared with the good condition of the upstream site. The Chironomidae species-level responses in the three downstream sites provided evidence of differences in biotic impairments, which were not evident with the family-level taxonomic data at these sites, thus highlighting the importance of species identification in freshwater biomonitoring. The family-level traits-based approach (TBA) showed that macroinvertebrates with gills and lungs were more abundant at the upstream site, decreasing markedly at the downstream sites. The relative abundance of macroinvertebrates relying on aerial and tegument respiration increased at the downstream sites compared with the upstream sites. The results of the family-level TBA highlighted the inextricable link between the traits-based approach (TBA) and taxonomic identification, clearly showing that the TBA is additional to, and not an alternative to, taxonomic recognition because important traits, e.g. reproductive cannot be used at a coarse taxonomic identification. A novel chironomid species traits-based functional strategies approach developed in this study, based on species combining similar sets of traits, proved sensitive in diagnosing the main abiotic water physico-chemical stressors. The functional traits responded predictably to deteriorating water quality and provided an adaptive and mechanistic basis for interpreting chironomid species occurrences at the four sampling sites, providing insight into why certain chironomid species occurred at one site but not at the other. Chironomid deformities provided evidence of sub-lethal in-stream biological response to deteriorating water quality. A newly developed deformity-based extended toxic score index proved sensitive, enabling the discrimination of the sampling sites, indicating that a biomonitoring tool based on sub-lethal effects could be used to assess the effects of deteriorating water quality before it reached lethal levels. Empirical evidence based on the taxonomic, traits and sub-lethal responses suggested that the changes in macroinvertebrate community structure were caused chiefly by the discharge of wastewater effluents into the river. This was supported by the model-stream ecosystem results indicating significant effects of effluents on the macroinvertebrate community structure, similar to the observed in-stream responses. The model stream results indicated that improved physico-chemical effluent quality compliance after 50% effluent dilution did not significantly reduce the effects of the effluent on the macroinvertebrate communities, showing that ecologically-based methods rather than physico-chemical measures alone are necessary to assess effluent quality. Finally, the results of the multi-criteria approach were integrated to propose tools to manage environmental water quality in the Swartkops River, and the benefits of the study were highlighted in the context of biomonitoring in South Africa.
Keywords: Water -- Pollution -- South Africa -- Swartkops River; Water quality biological assessment -- South Africa -- Swartkops River; Environmental toxicology -- South Africa -- Swartkops River; Environmental monitoring -- South Africa -- Swartkops River; Aquatic invertebrates -- Effect of water pollution on -- South Africa -- Swartkops River; Chironomidae -- Effect of water pollution on -- South Africa -- Swartkops River; Freshwater ecology -- South Africa -- Swartkops River